Application of Ecological Architecture Principles in Eco Resort Design at Pemenang, Lombok - Subagya, Surya; Trimarianto, Ciptadi (Journal of A Sustainable Global South; Vol 1 No 2 (2017): August 2017DO - 10.24843/jsgs.2017.v01.i02.p02, 2017)
Lombok Island seems to be a favorite holiday destination for international and domestic tourists, because it has many tourists destinations, one of which is North Lombok Regency. This condition greatly impact on increasing regional income, individual of communities from service accommodation to tourist. However, judging from the interest of tourist visits which increase every year, the avaibility of facilites in terms of quantity and quality has not been balanced. For example, resort as a form of tourism accommodation are the most sought after by tourist, because the have the most complete facilities to pamper tourist while enjoying the beauty of the sorrounding environment. In fact, the condition of tourism accommodation especially in the sub-district of Pemenang can be said to have not developed according to the demand and needs of tourist. The existence of resorts as a place to serve tourists in the sub-district of Pemenang is very minimal, this can be said because the number of accommodation is dominated by homestay class which in general has incomplete facilities. Beside that, it needs to be supported by special treatment in planning a resort with an eco-architecture approach to reduce the enviromental impact of planning this resort. This approach in planning eco-resort is combined with combining the local architecture to be in harmony with the conditions and atmosphere of the sorrounding environment. So, tourists can be take a vacation and relax while feeling the atmosphere of the sorrounding environment that is presented in this tourist accommodation Index Terms — resort, eco architecture, reduce, local of architecture, environment.